Pengaruh Profitabilitas, Kepemilikan Institusional dan Umur Perusahaan terhadap Integrated Reporting - Uyun Sundari; Ratno Agriyanto; Dessy Noor Farida (Eksos, 2020)
This research was conducted to determine the effect of profitability, institutional ownership and company age on integrated reporting. Type of research is quantitative with multiple linear regression data analysis techniques using the SPSS application. The data tested is secondary data. The population of this study is mining companies listed on the Indonesia Stock Exchange with the period 2016-2018. The sample uses a purposive sampling method which amounts to 48 samples. The results of this study indicate that first, profitability and institutional ownership have no effect on integrated reporting. Second, the age of the company affects the integrated reporting. Third, simultaneous profitability, institutional ownership and age of the company affect the integrated reporting.